Clinical significance of spleen size in patients with heart failure. (14th October 2021) - Hiraiwa, H; Okumura, T; Sawamura, A; Kondo, T; Araki, T; Mizutani, T; Kazama, S; Kimura, Y; Shibata, N; Oishi, H; Kuwayama, T; Furusawa, K; et al.
Abstract: Background: The spleen is an important organ that stores blood, releases erythrocytes or monocytes, and destroys no-longer-needed platelets. It can reserve 20–30% of the total blood volume, and its size is reduced in hypovolemic shock. However, the clinical significance of the spleen size in patients with heart failure (HF) remains unclear. Purpose: The purpose of this study was to investigate the relationship between spleen size, hemodynamic parameters, and prognosis in patients with HF. Methods: A total of 219 patients with clinically stable HF were enrolled. All patients underwent right heart catheterisation and computed tomography. The spleen size was measured using computed tomography volumetry. In addition, spleen volume was assessed using the spleen volume index (SVI), corrected for body surface area. Cardiac events were composite endpoints of cardiac death, hospitalisation for worsening HF, fatal arrhythmias, implantation of cardiac devices, implantation of left ventricular assist devices, and unexpected percutaneous coronary intervention or cardiac surgery. Spearman's rank correlation coefficient was used to examine the relationship between spleen volume and hemodynamic parameters. Multivariate Cox hazard regression models were used to investigate whether SVI was an independent determinant of cardiac events. Results: Of the 219 patients (median age, 54 [interquartile range] 46–64 years), 145 (66%) were males. The median (interquartile range) spleen volume and SVI was 118.0 (91.5–156.0) mL and 67.8 (54.9–87.2) mL/m 2, respectively. SVI was positively correlated with cardiac output (r=0.269, P<0.001), and negatively correlated with systemic vascular resistance (r=−0.302, P<0.001) (Figure 1). A total of 70 cardiac events were observed, and the optimal cut-off value of SVI for cardiac events was 68.9 mL/m 2 in the receiver operating characteristic analysis. Patients were divided into two groups: low-SVI (n=107, <68.9 mL/m 2 ) and high-SVI groups (n=112, ≥68.9 mL/m 2 ). Blood adrenaline concentration was higher in the low-SVI group than in the high-SVI group (0.039 [0.020–0.057] ng/mL vs 0.026 [0.014–0.044] ng/mL, P=0.004). The low-SVI group had more cardiac events than the high-SVI group (log-rank test, P<0.001) (Figure 2). In the multivariate Cox proportional hazard model, the low-SVI group was an independent predictor of cardiac events, even when adjusted for the conventional validated HF risk score, blood catecholamine levels, and hemodynamic parameters. Conclusion: The spleen size may affect the prognosis in patients with HF, reflecting haemodynamics, including systemic circulating blood volume status and sympathetic nerve activity. Funding Acknowledgement: Type of funding sources: None.